A Study on Scenic Road according to Place Concept and Cognition Method Focusing on cases of Korea and Germany - Lee, Ja-Hyun; Lee, Jun-Gi Lee; Lee, Kyung-Hee (International Journal of Engineering and Technology, 2018)
Background/Objectives: It is necessary to improve the environment of the road, which is the main cause of air pollution, to construct roads that demand sustainable development and pursue a valuable environment.Methods/Statistical analysis: The infrastructure is created by the arrangement of the linear space as the path is provided to the dotted tourist spot. Thus, we have an identity that links places and places with nature. In order to recognize these places, Kevin Lynch 's urban image concept and detail characteristics analysis method were analyzed. The relationship between the forms of the road and other places was identified.Findings: The two landscape roads have a distinctly different route. This shape makes it easier to understand the meaning of the place and the landscape and focus on the relationship. Through the morphological meaning, we were able to identify the elements that can distinguish between urban history and planned cities or spontaneous cities. The landscape of Korea, which is laid horizontally along the coastline, can be regarded as a 'soft space', and Germany, which has a stronger image in the urban structure leading from the scenery road to the aisle, can be regarded as 'hard space'.Analysis of the detailed characteristics of the city can help to grasp the distance and relationship between the road and the place, and helps to understand the urban structure. It can be seen that the historical and cultural tourism center where the place is important shows the city more clearly, and the scenic road with the high scenery is more clearly drawn.Improvements/Applications: If the environment is preserved and the value of the resource is increased, there will be a positive impact of the road environment. However, a plan that excludes the place name property is not effective.Â Â